Safety and efficacy of baricitinib at 24 weeks in patients with rheumatoid arthritis who have had an inadequate response to methotrexate. Issue 2 (27th November 2014) - Keystone, Edward C; Taylor, Peter C; Drescher, Edit; Schlichting, Douglas E; Beattie, Scott D; Berclaz, Pierre-Yves; Lee, Chin H; Fidelus-Gort, Rosanne K; Luchi, Monica E; Rooney, Terence P; Macias, William L; Genovese, Mark C
Abstract : Objectives: To investigate baricitinib (LY3009104, formerly INCB028050), a novel, oral inhibitor of JAK1/JAK2 in patients with moderate to severe rheumatoid arthritis (RA) despite treatment with methotrexate. Methods: In this phase IIb study, 301 patients were randomised 2:1:1:1:1 to receive once daily doses of placebo or 1, 2, 4 or 8 mg baricitinib for 12 weeks. Patients assigned to 2, 4 and 8 mg baricitinib continued blinded treatment for an additional 12 weeks. Patients assigned to placebo or 1 mg baricitinib were reassigned to 2 mg twice daily or 4 mg once daily baricitinib between weeks 12–24. The primary endpoint was the proportion of patients in the combined 4 and 8 mg groups achieving an American College of Rheumatology 20% (ACR20) response versus placebo at week 12. Results: Significantly more patients in the combined baricitinib 4 and 8 mg groups compared with placebo achieved an ACR20 response at week 12 (76% vs 41%, p<0.001). At week 12, significant differences versus placebo were also observed in patients achieving ACR50, ACR70 and remission as measured by Disease Activity Score for 28-joint counts, Clinical Disease Activity Index and Simplified Disease Activity Index. Patients receiving 2, 4, or 8 mg baricitinib maintained or improved in all measures through 24 weeks. Similar proportions of patients experienced at least one adverse event in the placebo and baricitinib groups. Serious infections developed in three patients receiving baricitinib. No cases of tuberculosis, herpes zoster, opportunistic infections or deaths were reported. Dose-dependent decreases in haemoglobin were observed with baricitinib. Conclusions: Baricitinib improved the signs and symptoms of RA in methotrexate inadequate responders with active disease. Baricitinib was well tolerated with no unexpected safety findings through week 24. Trial registration number: NCT01185353.